PARENTERAL FEEDING COMPLICATIONS IN PEDIATRICS - R. F. Tepaev; A. N. Kiryanova; A. S. Belousova; E. I. Ilyichyova; A. V. Lazareva; O. A. Kryzhanovskaya (Union of pediatricians of Russia, 2013)
The article is dedicated to parenteral feeding - infusion therapy aimed at introducing water, macro- and micronutrients in concordance with body needs. Different parenteral feeding types are described: complete, partial and additional. It shows that balanced parenteral feeding allows providing the child's body with the sufficient amount of amino acids, carbohydrates, fats and energy required to maintain a baseline energy level and correct a preceding nutritive insufficiency. Protein-energy homeostasis is the basis for vital activity of the body; it determines the inflammatory response activity, immune status adequacy, disease duration and severity and disease prognosis (to a considerable degree). Long-term parenteral feeding is associated with complications of varying severity: from transitory and mild to severe, requiring operative intervention and liver transplantation. The command of modern recommendations allows a practicing doctor to successfully overcome issues associated with long-term parenteral feeding. The article presents modern data on diagnostics, prevention and treatment of parenteral feeding complications.